The Influence of Gamification, User Experience and E-Service Quality on Repurchase Intention with Customer Satisfaction as an Intervening Variable on Tokopedia Consumers in Medan City - Iin Angelina Sinaga; Arlina Nurbaity Lubis; Yeni Absah (Indonesian Journal Publisher, 2025)
The development of information technology has encouraged a shift in consumer behavior from conventional to online shopping. Although the e-commerce industry generally shows growth, Tokopedia, as one of the major platforms, has experienced a decline in the number of visitors. According to data from iPrice, Tokopedia's monthly visitors decreased from 158,136,700 in 2021 to 96,933,334 in 2023. This study aims to examine and analyze the influence of gamification, user experience, and e-service quality on repurchase intention through customer satisfaction as a mediating variable among Tokopedia users in Medan City. This is an associative study using a quantitative approach. The population in this study consists of Tokopedia consumers in Medan City who have the Tokopedia application and have made at least two online transactions through the application, with the exact total population being unknown. The sample comprises 225 respondents selected using purposive sampling, with criteria including a minimum age of 18 years and a minimum education level of senior high school (or equivalent). Data were analyzed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) method. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) method. The results indicate that gamification has a positive but not significant direct effect on customer satisfaction and repurchase intention among Tokopedia users in Medan City. User experience and e-service quality have a positive and significant direct effect on both customer satisfaction and repurchase intention. Additionally, customer satisfaction itself has a positive and significant direct effect on repurchase intention. Indirectly, user experience and e-service quality have a positive and significant influence on repurchase intention through customer satisfaction, while gamification shows a positive but not significant indirect effect through the same mediating variable.